(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of this work was to evaluate the impact of low rates of application of environmentally friendly organo-mineral soil amendments on grown under organic farming conditions dill’s green mass yield and it’s composition, including the content of polyphenolic compounds. Soil amendments were obtained based on forest logging residues – lignocellulosic biomass, after isolation of polyphenols by water-ethanol extraction and enrichment with silicon (Si)-containing inorganic oligomer in various mass ratios. Lignocellulosic biomass is rich in polyphenols which can damage the functionality of the bacterial cell membranes thus inhibiting the growth of soil microorganisms. Polyphenols can be isolated from the lignocellulosic substrate and evaluated in further studies for their potential to protect plants from pathogenic microorganisms. The influence of the prepared soil amendments on soil microorganisms was tested. Field experiments were carried out in a certified biological field intended for scientific purposes. It was shown that soil amendments have a beneficial effect on the yield (42%) and a slight influence on the composition of dill at low amendment application rates. The addition of soil amendments also contributed to insignificant changes in the amount of polyphenols. The soil amendments didn’t influence the soil microorganisms under study. The results confirmed the ability of the soil amendments based on the forest logging residues to activate dill growth.